Establishing a protocol for sorghum (Sorghum bicolor) gene transformation - Navrude, Spencer (Kansas State University, 2021)
Sorghum (Sorghum bicolor) is one of the most utilized crops in the world. Not only does it provide a staple food source for arid regions of the planet, it is also important for sustaining livestock production, as well as advancements in its use in biofuels. Despite the importance of sorghum for a large swath of the world, progress for using genetic transformation to develop more useful sorghum varieties has been far outpaced by other similar cereal crops. Thus, developing and improving a protocol to reliably transform sorghum is of great interest, in which the results will be beneficial to improving agricultural use all over the world. The objective of this study was to identify results of sorghum transformation from many sources and apply successful tissue culture and transformation techniques into one successful protocol. Positive control was established before transformation to guarantee embryo regeneration prior to inoculation. Two different media types were established and analyzed for their production and quality of callus and shoot regeneration. A comparison was made on two medium types, referred to as “B” media [2,4-D for callus induction and 6-Benzylaminopurine (BAP)/indole-3-acetic acid (IAA) for regeneration] and “S” media [2,4-D/BAP for callus induction and 2,4-D/BAP/thidiazuron (TDZ) for regeneration], respectively. Although both these medium types yielded viable plants with roots and shoots, B media was selected for its successes in callus induction and shoot regeneration. Calluses induced embryos in B media yielded shoots that were larger, more distinct, and easier to separate compared to calluses on S media. Once positive control was established, two bacterial strains, EHA101 and LBA4404, containing the same vector, SbGFPTSCENH3, were evaluated for their efficacy for targeted mutagenesis of sorghum using a CRISPR/Cas9 system. LBA4404 proved to be a more effective bacterial strain than EHA101 in transforming sorghum embryos, with little to no bacterial overgrowth, and higher rates of green callus and shoot emergence. Of all embryos inoculated with Agrobacterium, five plants were fully regenerated into a viable plant on herbicide selection pressure and then acclimated in the soil. To confirm transformation, polymerase chain reaction (PCR) and gel electrophoresis analysis were performed. Our initial result from gel electrophoresis analysis of the five plants indicated that all five plants appeared to be transgenic. After sequencing the genome of the plants, their sequences were aligned and matched with the genomes sequenced from the CENH3 construct and the extracted plasmid. Of the five plants, three of their genomes indicated a 98 to 99% match to both the CENH3 construct and the plasmid. Upon further inspection of the chromatogram results, errors were corrected in the initial results, which showed a 100% match for these three plants. Based on these results, we can confidently say that these three plants are transgenic.
Keywords: Sorghum transformation; Sorghum genetics